Manual and automated intima-media thickness and diameter measurements of the common carotid artery in patients with renal failure disease - Loizou, Christos P.; Kasparis, Takis; Lazarou, Theodoros; Pattichis, Constantinos S.; Pantziaris, Marios (My University, 2014)
The objective of this study was to investigate differences in intima-media thickness (IMT) and diameter (D) measurements of the common carotid artery (CCA) in ultrasound imaging in normal subjects and renal failure disease (RFD) patients. Manual measurements by two experts and automated segmentation measurements (based on snakes and active contour models (ACM)) were carried out on 73 normal subjects, and 80 RFD patients. Statistical analysis was carried out using the Wilcoxon rank-sum test at p<0.05. Results demonstrated that the mean IMT and D measurements were significantly higher for the RFD group versus the normal group. Moreover, there was no significant difference between the manual and automated measurements. The ACM segmentation was slightly more accurate than segmentation based on snakes. Further work is needed to validate these findings on a larger group of subjects.
Keywords: Carotid diameter; Common carotid artery; Intima-media thickness; Renal failure disease; Segmentation; Ultrasound imaging